Jobless parents, unhealthy children? How past exposure to parental joblessness influences children's future health - Irma Mooi-Reci; Mark Wooden (Elsevier, 2022)
Rationale: Despite a growing body of work investigating the combined effects of maternal and paternal joblessness for children's outcomes, very little is known about the long-term effects of parental joblessness on children's health, and especially health during adulthood. Objective: The primary objective of this study is to directly test whether exposure to parental joblessness during childhood and early adulthood has adverse consequences for health in later years. This study also explores whether family resources, time inputs and family harmony mediate this relationship. Methods: Multilevel generalized structural equation models describing processes influencing child health outcomes in later life are estimated using longitudinal data from 19 waves of the Household, Income and Labour Dynamics in Australia Survey (N = 2875 individuals and 22,942 person-year observations). Results: Parental joblessness, especially when experienced over a protracted period, is found to impose a penalty on children's mental health in later life, which is mostly not mediated by other variables. A significant negative association with general health is also found, but in this case family income and family harmony play a more important mediating role. Conclusion: The results suggest that it is not parental job loss per se that matters, but parents not being able to quickly find alternative employment. It is only children in families where joblessness is protracted and long-lasting who are at serious risk of long-term health problems. In sum, our results imply that the parental outcome that is most important for children's later health, and especially their mental health, is continuous paid employment. Such findings provide support for a jobs-first policy emphasis.